1987
DOI: 10.1007/bf00543979
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the central effects of the H1-antagonist, loratadine

Abstract: Effects of loratadine (10, 20 and 40 mg) on visuo-motor coordination, dynamic visual acuity, short-term memory, digit symbol substitution, and on subjective assessments of mood were tested before, and 0.5, 1.5, 3.5 and 5.5 h after ingestion by 6 healthy female adults. There were no effects of 10 or 20 mg loratadine. With 40 mg loratadine the number of substitutions on the digit symbol test was reduced 5.5 h after ingestion, and on dynamic visual acuity response time was increased at 3.5 h and the number of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…However, these newer antihistamines penetrate the brain slowly and may cause sedation and CNS dysfunction. This occurs frequently at doses just above the recommended ones, as shown for terfenadine 240 mg [34,35], cetirizine 20 mg [36,37] and loratidine 40 mg [35,38,39]. Some studies have reported slight impairment of some measurements at therapeutic dose [36,39,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…However, these newer antihistamines penetrate the brain slowly and may cause sedation and CNS dysfunction. This occurs frequently at doses just above the recommended ones, as shown for terfenadine 240 mg [34,35], cetirizine 20 mg [36,37] and loratidine 40 mg [35,38,39]. Some studies have reported slight impairment of some measurements at therapeutic dose [36,39,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Drugs such as terfenadine, astemizole, loratadine and mequitazine which are either nonsedating or non-sedating at certain therapeutic doses (Clarke & Nicholson, 1978;Nicholson, 1982;Nicholson & Stone, 1982;1983;Bradley & Nicholson, 1987) usually exhibit poor penetration of the central nervous system, and in some cases possibly lower affinity for central Hl-receptors than for peripheral sites (Quach et al, 1980;Barnett et al, 1984;Ahn & Barnett, 1986;McQuade et al, 1990). The stereoselective activity of two potent antihistamines shown in the present study in man provides further support to the belief that the histaminergic system is concerned with the regulation of alertness.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the newer antihistamines are able to penetrate the brain and may cause CNS side effects, especially at doses just above the recommended ones, as shown for terfenadine 240 mg [28,29], cetirizine 20 mg [30], loratadine 40 mg [31,32], bilastine 80 mg [33] or rupatadine [11]. On the other hand, several studies have reported slight impairment of some measurements at therapeutic dose [30][31][32][34][35][36], and even the minimal potential of a drug to produce sedation is important, since it might add to or potentiate the sedative effect of another drug or alcohol taken concomitantly.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have reported slight impairment of some measurements at therapeutic dose [30][31][32][34][35][36], and even the minimal potential of a drug to produce sedation is important, since it might add to or potentiate the sedative effect of another drug or alcohol taken concomitantly. In a previous study carried out in our centre, single oral doses of rupatadine 10 mg in combination with alcohol did not produce more cognitive and psychomotor impairment than alcohol alone [12].…”
Section: Discussionmentioning
confidence: 99%